Creative Corporate Communication in Social Media – How to Effectively Build Relations and Receive High Quality Resumes From Younger Generations - Barbara Drapała (Studia i Materiały)
Nowadays, companies increasingly often face the dilemma of how to reach and recruit younger people. The goal of this paper is to present different values, important for every generation still active on the labour market, and to present the content attributes influencing the response to recruitment posts and the number of obtained resumes. The paper uses quality analyses in the form of a case study in order to analyse social media recruitment campaigns of the chosen marketing agency. The discussion is divided into three parts. The first part covers the analysis of the form, type of content and message, used by a given brand in recruitment announcements posted in social media. As a result, the content attributes were identified (format, application form, readability, offer length, use of hashtags and emojis, cohesion of the message and analysis of requirements, benefits and added values). The second part covers the analysis of results of these paid recruitment announcements. The third part uses a deductive approach in a form of empirical analysis covering the preliminary logical analysis of results (Zaborek, 2007). By means of analytic generalisation, the author wants to present preliminary conclusions regarding the effectiveness of recruitment campaigns targeted at young generations and demonstrate interrelations between individual content attributes and engagement of users in the posts and resumes received by the company from potential candidates. The analysis indicates that younger generations (Generations Y and Z) do not share the same values as the older generations (the so-called Baby Boomers and Generation X). This is probably due to the fact that the younger generations entered the labour market at different economic times, were brought up in a different spirit and differently function in the world.